Curcuma longa (Turmeric) for Prevention of Capecitabine-Induced Hand-Foot Syndrome: A Pilot Study. (3rd September 2018) - Scontre, Vanessa Armenio; Martins, Janine Capobiango; de Melo Sette, Claudia Vaz; Mutti, Haila; Cubero, Daniel; Fonseca, Fernando; Del Giglio, Auro
ABSTRACT: Hand-foot syndrome (HFS) is common and frequently occurs in the first cycle of treatment in approximately 40% to 50% of patients who receive capecitabine. Turmeric ( Curcuma longa ) is a plant used in Ayurvedic medicine with clinical activity in various inflammatory conditions. Our objective was to evaluate whether turmeric was active for the prevention of capecitabine-induced HFS. We included patients older than 18 years of age without previous exposure to capecitabine who were scheduled to receive this medication. Before starting treatment, after three weeks and at the end of six weeks, we evaluated dermatologic toxicity, conducted quality-of-life questionnaires (EORTC-QLQC30 and DLQI) and collected serum inflammatory biomarkers (inerleukin-6 (IL-6), tumor necrosis factor-a (TNF-a), C-reactive protein (CRP), and albumin). We administered turmeric at a dose of 4 g/day (2 pills 12 hours apart) starting at the beginning of capecitabine treatment and lasting six weeks. We included 40 patients whose mean age was 62 years. Most were female (80%), 52% had breast cancer, and 47.5% had GI tumors. After the first cycle of capecitabine treatment, we observed that 11 of 40 patients developed HFS (27.5%; 95% CI [15, 42]), whereas four patients developed HFS equal or superior to grade 2 (10%; 95% CI [3.3, 23]). We did not find any correlations between the inflammatory markers tested and HFS. We show that turmeric combined with capecitabine seems to produce a lower rate of HFS, especially grade 2 or higher. These findings need to be reproduced in larger controlled studies.